Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To determine which point lies on the line described by the equation [tex]\( y + 3 = 2(x - 1) \)[/tex], we need to test each point by substituting the coordinates [tex]\( (x, y) \)[/tex] into the equation and verifying if the equation holds true. Let’s simplify the line equation first:
[tex]\[ y + 3 = 2(x - 1) \][/tex]
Rewriting it in the standard form [tex]\( y \)[/tex] as a function of [tex]\( x \)[/tex]:
[tex]\[ y + 3 = 2x - 2 \][/tex]
Subtracting 3 from both sides, we get:
[tex]\[ y = 2x - 5 \][/tex]
Now we will test each point:
A. (1, -3)
[tex]\[ y = 2(1) - 5 \][/tex]
[tex]\[ -3 = 2 - 5 \][/tex]
[tex]\[ -3 = -3 \quad \text{(True)} \][/tex]
B. (0, 0)
[tex]\[ y = 2(0) - 5 \][/tex]
[tex]\[ 0 = -5 \quad \text{(False)} \][/tex]
C. (-1, -6)
[tex]\[ y = 2(-1) - 5 \][/tex]
[tex]\[ -6 = -2 - 5 \][/tex]
[tex]\[ -6 = -7 \quad \text{(False)} \][/tex]
D. (2, 1)
[tex]\[ y = 2(2) - 5 \][/tex]
[tex]\[ 1 = 4 - 5 \][/tex]
[tex]\[ 1 = -1 \quad \text{(False)} \][/tex]
E. (1, -4)
[tex]\[ y = 2(1) - 5 \][/tex]
[tex]\[ -4 = 2 - 5 \][/tex]
[tex]\[ -4 = -3 \quad \text{(False)} \][/tex]
F. (2, 9)
[tex]\[ y = 2(2) - 5 \][/tex]
[tex]\[ 9 = 4 - 5 \][/tex]
[tex]\[ 9 = -1 \quad \text{(False)} \][/tex]
From the calculations, the only point that satisfies the equation [tex]\( y + 3 = 2(x - 1) \)[/tex] is:
A. (1, -3)
Therefore, the point [tex]\( (1, -3) \)[/tex] lies on the line described by the equation.
[tex]\[ y + 3 = 2(x - 1) \][/tex]
Rewriting it in the standard form [tex]\( y \)[/tex] as a function of [tex]\( x \)[/tex]:
[tex]\[ y + 3 = 2x - 2 \][/tex]
Subtracting 3 from both sides, we get:
[tex]\[ y = 2x - 5 \][/tex]
Now we will test each point:
A. (1, -3)
[tex]\[ y = 2(1) - 5 \][/tex]
[tex]\[ -3 = 2 - 5 \][/tex]
[tex]\[ -3 = -3 \quad \text{(True)} \][/tex]
B. (0, 0)
[tex]\[ y = 2(0) - 5 \][/tex]
[tex]\[ 0 = -5 \quad \text{(False)} \][/tex]
C. (-1, -6)
[tex]\[ y = 2(-1) - 5 \][/tex]
[tex]\[ -6 = -2 - 5 \][/tex]
[tex]\[ -6 = -7 \quad \text{(False)} \][/tex]
D. (2, 1)
[tex]\[ y = 2(2) - 5 \][/tex]
[tex]\[ 1 = 4 - 5 \][/tex]
[tex]\[ 1 = -1 \quad \text{(False)} \][/tex]
E. (1, -4)
[tex]\[ y = 2(1) - 5 \][/tex]
[tex]\[ -4 = 2 - 5 \][/tex]
[tex]\[ -4 = -3 \quad \text{(False)} \][/tex]
F. (2, 9)
[tex]\[ y = 2(2) - 5 \][/tex]
[tex]\[ 9 = 4 - 5 \][/tex]
[tex]\[ 9 = -1 \quad \text{(False)} \][/tex]
From the calculations, the only point that satisfies the equation [tex]\( y + 3 = 2(x - 1) \)[/tex] is:
A. (1, -3)
Therefore, the point [tex]\( (1, -3) \)[/tex] lies on the line described by the equation.
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.